Born-Oppenheimer approximation in optical cavities: from success to breakdown - Fábri, Csaba; Halász, Gábor J.; Cederbaum, Lorenz S.; Vibók, Ágnes (Chemical science, 2021)
The coupling of a molecule and a cavity induces nonadiabaticity in the molecule which makes the description of its dynamics complicated. For polyatomic molecules, reduced-dimensional models and the use of the Born-Oppenheimer approximation (BOA) may remedy the situation. It is demonstrated that contrary to expectation, BOA may even fail in a one-dimensional model and is generally expected to fail in two- or more-dimensional models due to the appearance of conical intersections induced by the cavity.